Podział ryzyka transakcji kredytowej jako element działalności instytucji poręczeń kredytowych dla małych i średnich przedsiębiorstw - Adamek, Jacek (The Division of Credit Transaction Risk as An Element of the Credit Guarantee Institution's Activity for Small and Medium Enterprises, 2005)
Guarantee entities, while offering their services, are open to several kinds of different risks. It seems that the most serious threat for activities of these institutions becomes the risk resulting from the requirement of covering the guarantee beneficiary's credit commitments towards the financing institution (such risk should be referred to as the credit risk). Rational behaviour of the guarantee institution imposes taking up certain activities (risk steering), which optimize these threats. Transfer of risk over to the parties of the guarantee transaction is one of them. The objective of the above paper is to present the solutions used by the guarantee units with regard to the above issue. Its contents is based on the analysis of literature describing experiences of the guarantee institutions functioning in different parts of the world.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 200-212